PENGARUH KINERJA KEUANGAN, PROFITABILITAS, GOOD CORPORATE GOVERNANCE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN MINUMAN DAN MAKANAN - Inge Octavidiani Withiono; Ismunawan (PROSEDING, 2022)
The purpose of this research was to determine the effect of financial performance, profitability, GCG and dividend policy on the value of beverages and food companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. This study uses purposive sampling, namely 11 food and beverages companies listed on the Indonesia Stock Exchange (IDX) with a sample of 44. This research is a quantitative study with secondary data in the form of financial statements of food and beverage companies that have been processed using multiple linear regression analysis methods. The results of this study indicate that financial performance has a positive influence on firm value (ROE), profitability has no effect on firm value (ROA), GCG has a positive influence on firm value (KM) and dividend policy has a positive effect on company value (DPR).